Sevoflurane and its use in veterinary practice - MANTZIARAS (Γ. ΜΑΝΤΖΙΑΡΑΣ) G. I.; KOSTOMTSOPOULOS (Ν. ΚΩΣΤΟΜΗΤΣΟΠΟΥΛΟΣ) N.; RAPTOPOULOS (Δ. ΡΑΠΤΟΠΟΥΛΟΣ) D. (Journal of the Hellenic Veterinary Medical Society, 2017)
In clinical practice die anaesthetist often faces die dilemma of choosing die best fitting agem from a wide variety of injectable and volatile anaesdietic drugs. Meanwhile, die continuous progress of anaesthesiology offers new drugs and modern Techniques, making die final choice even more difficult. Sevoflurane is a new volatile anaesthetic agent, which is nowadays increasingly used in veterinary anaesthesia. It is a fluorinated derivative of methyl- isopropyl-ether. At room temperature it is a non-flammable, non-explosive, colourless liquid, with a pleasant smell. The aim of this review article is to present the basic attributes of sevoflurane and its use in veterinary practice. Its most important physical and chemical properties and their clinical implications, as well as its pharmacokinetics, pharmacodynamics, metabolism and potential toxicity are presented. Furthermore, sevoflurane is compared with other commonly used volatile anaesthetic agents and its use in anaesthesia of various companion, large and laboratory animals is discussed. Examples of sevoflurane administration, and of possible combinations with other drugs used in veterinary anaesthesia, are also given.